Minimizing competition by removing elephants from a degraded Ngulia rhino sanctuary, Kenya - Benson Okita-Ouma; Dominic Mijele; Rajan Amin; Francis Gakuya; David Ndeereh; Isaac Lekolool; Patrick Omondi; Daniel Woodley; Moses Litoroh; Juma Bakari; Richard Kock (Pachyderm)
The Ngulia rhino sanctuary located in the central part of Tsavo West National Park (NP) is completely fenced within an area of 88 km 2 following its expansion from 62 km 2 in May 2007. It has been one of the more successful areas for the protection and breeding of black rhinos in Kenya since its creation in 1986, and has succeeded in re-establishing a productive breeding nucleus of rhinos within a larger protected area with very considerable potential for further expansion to a large, genetically viable population. The sanctuary therefore plays a key role in the conservation of the eastern black rhinoceros (Diceros bicornis michaeli).